Systematic evaluation of circulating inflammatory markers for hepatocellular carcinoma. (29th August 2016) - Chan, Stephen L.; Chan, Anthony W.H.; Chan, Allen K.C.; Jian, Peiyong; Mo, Frankie; Chan, Charles M.L.; Mok, Kevin; Liu, Calvin; Chong, Charing C.N.; Chan, Anthony T.C.; Mok, Tony; Yeo, Winnie
Abstract: Backgrounds & Aims: A number of circulating inflammatory factors are implicated in the pathogenesis and prognostication of hepatocellular carcinoma (HCC). We aim to evaluate the prognostication of multiple serum inflammatory factors simultaneously and develop an objective inflammatory score for HCC. Methods: A prospective cohort of 555 patients with HCC with paired serum samples was accrued from 2009 to 2012. The blood levels of conventional inflammatory markers, namely C‐reactive protein (CRP), albumin, neutrophils, lymphocytes and platelet, were determined, and 41 other exploratory markers were measured by a multiplex assay. The prognostication and interaction of markers were determined by univariate and multivarite analyses. Results: The cohort was randomly divided into training cohort (n=139) and validation cohort (n=416). There were no differences in baseline characteristics between the two cohorts. In the training cohort, independent prognostic factors for overall survival included CRP (hazard ratio [HR] 1.107; P =.003), albumin (HR 0.953; P =.032) and interleukin‐8 (HR=5.816; P <.001). We have modified the existing inflammation‐based index (IBI) by adding serum interleukin‐8 level. The modified IBI could stratify patients into four groups with distinct overall survival ( P <.001). The results were also validated in the validation cohort. When compared with IBI and other conventional inflammatory markers, the modified IBI had better prognostic performance with higher c‐index and homogeneity likelihood ratio chi‐square. Conclusions: Among the conventional and exploratory circulating inflammatory markers, higher CRP, lower albumin and higher interleukin‐8 were independent prognosticators. By combining these factors, a simple and accurate inflammatory index could be constructed.